Influence of Work Motivation and Communication on Employee Morale at Rimba Jimbaran Bali Hotel - Sumerta, I Ketut Eli; Purnama Dewi, Desak Made; Juliantini, Ni Made (Jurnal Manajemen Pelayanan Hotel, 2023)
This study aims to determine the effect of work motivation and communication on employee morale. This research was conducted at Rimba Jimbaran Bali Hotel. The population in this study were all employees of Rimba Jimbaran Bali Hotel, totaling 162 employees. The sample was determined using the Slovin formula and the proportionate random sampling method with a total sample of 62 employees. Data collection was carried out by distributing questionnaires. The data analysis technique used was multiple linear regression analysis. The analysis techniques used were validity and reliability tests, classic assumption test, multiple linear regression analysis, multiple correlation analysis, multiple determination analysis t test and F test. Data analysis conducted using SPSS (Statistical Package for Social Science) for Windows, version 26.0. From the results of statistical analysis, the regression coefficient value between work motivation and employee morale is 0.455; t-count value is greater than t-table (5.004>1.671). The regression coefficient value between communication and employee morale is 0.359; t-count value is greater than t-table (3.678>1.671). The multiple linear regression equation is Y= 1.061 + 0.455(X1) + 0.359(X2); F-count value is greater than F-table (60.870>3.15). This means that the independent variable has a positive and significant influence on the dependent variable. From the results of this study it can be concluded that there is a positive and significant influence between Work Motivation and Communication on Employee Morale either partially or simultaneously. Keywords: Work Motivation, Communication, Employee Morale